PEMERTAHANAN RITUAL NGABEN ADAT DI DESA ADAT SIDATAPA KECAMATAN BANJAR KABUPATEN BULELENG - Pramana, Komang Agus Budhi Arya (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Through this research, researchers seek to explore, explore, and find reasons behind the maintenance, procedures for implementation, and the implications of Ngaben Adat (tradition) Nangun in Sidetapa village. The data in this study were obtained through interviews, observations, and document studies. Furthermore, the data that has been collected will be analyzed by qualitative descriptive analysis. The results of this study found that: (1) the reasons for maintaining the traditional Ngaben ritual in the village of Sidetapa, namely: (a) the maintenance of the traditional house, (b) the maintenance of the banten bali taksu, (c) the maintenance of the banten Bangun urip, (d) the maintenance of the unity of all wangsa, (e) the existence of holy people, and (f) ancestral sanctions and Ida panembahan, (2) the traditional nangun cremation procession is carried out in a series, namely: (a) mesadok (reporting), (b) submission of banten batun lis, (c) the nanceb ceremony, (d) the creating of karangan, (e) the mebersih ceremony, and (f) the culmination of the Ngaben ceremony which ended with the ngapisin ceremony led by Jro Balian Gede, (3) The traditional Ngaben ritual of nangun in Sidatapa village has psychological, moral, and social implications.